2020
DOI: 10.1016/j.ensm.2020.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the effect of vacancies and electropositive cations on the anionic redox processes in Na based P2-type layered oxides

Abstract: Decoupling the effect of vacancies and electropositive cations on the anionic redox processes in Na based P2-type layered oxides. (2020) Energy Storage Materials, 31. 146-155.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…[9][10][11][12][13] But with 3d metals, anionic redox is solely reported with non-stoichiometric P2/P3type NaxAyM1-yO2 (0 < x < 1, y < 1) phases where the non-bonding O 2p orbitals are made available by increasing the O/M ratio compared to LiMO2 using Li + / Mg 2+ / Zn 2+ or vacancies as the A cation instead of Na + . [14][15][16][17][18][19][20] However, practical wise P2/P3 phases fall short in achieving high energy density target, because of their Na deficiency. 21 Hence, the standing challenge resides in the synthesis of anionic-redox active sodium layered oxides consisting of 3d transition metals while having full sodium stoichiometry (Na(A,M)O2 with Na/(A,M) = 1).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] But with 3d metals, anionic redox is solely reported with non-stoichiometric P2/P3type NaxAyM1-yO2 (0 < x < 1, y < 1) phases where the non-bonding O 2p orbitals are made available by increasing the O/M ratio compared to LiMO2 using Li + / Mg 2+ / Zn 2+ or vacancies as the A cation instead of Na + . [14][15][16][17][18][19][20] However, practical wise P2/P3 phases fall short in achieving high energy density target, because of their Na deficiency. 21 Hence, the standing challenge resides in the synthesis of anionic-redox active sodium layered oxides consisting of 3d transition metals while having full sodium stoichiometry (Na(A,M)O2 with Na/(A,M) = 1).…”
Section: Introductionmentioning
confidence: 99%
“…The long plateau near the high potential of 3.8 V belongs to the typical phase transition of P2‐type layered cathode material (from P2 to O2, [ 33 ] Z, [ 28 ] OP4, [ 34 ] etc.). The reasons for the phase transition can be summarized as follows: 1) the slip of the TM layer, [ 35 ] 2) the transformation of Na + vacancy ordering, [ 36 ] and 3) the Jahn–Teller effect. [ 23 ] Compared with the NaClO 4 ‐based cell, the plateau in the NaPF 6 ‐based cell is shorter and the polarization is smaller.…”
Section: Resultsmentioning
confidence: 99%
“…for which a third of the TM layers can be filled by mono-or divalent elements such as Li [17][18][19][20][21][22][23][24][25][26][27][28][29], Mg [46][47][48][49][50][51][52][53][54][55][56], and Zn [57][58][59] to induce an average oxidation state of Mn of 4+. Hence, the extraction of sodium ions in the structure is not theoretically possible because of the difficulty of the oxidation of Mn 4+ to higher valence states in an octahedral environment, in which the electrolyte does not decompose.…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 99%
“…According to their combined studies of O K-edge X-ray absorption (XAS) and resonant inelastic X-ray scattering (RIXS), the voltage plateau above 4.1 V, with the phase transition from P2 to O2 or OP4, can be attributed to the reaction of the electrondeficient oxide ion (oxygen hole) in the 2p orbital interacting with the Mg 2+ 3s and Mn 4+ 3d orbitals. Charge compensation was achieved via this reaction, resulting in the extraction of sodium ions from Na 2/3 [ ]O 2 , with not only the absence of the phase transition but a higher capacity than that of the vacancy-free compound [55]. DFT calculation indicated that the oxygen close to the vacancies (Na-O-□ Mg ) provides more charge than the oxygen coordinated with Mg (Na-O-Mg) on charge, resulting in more charge compensation with the presence of vacancies that induce the lower-level voltage plateau for the oxygen reaction.…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 99%
See 1 more Smart Citation